Talking about firearm injury prevention with patients: a survey of medical residents - Rocco Pallin; Sara Teasdale; Alicia Agnoli; Sarabeth Spitzer; Rameesha Asif-Sattar; Garen J. Wintemute; Amy Barnhorst (BMC Medical Education, 2022)
Abstract Background Firearm injury and death are significant public health problems in the U.S. and physicians are uniquely situated to help prevent them. However, there is little formal training in medical education on identifying risk for firearm injury and discussing safe firearm practices with patients. This study assesses prior education, barriers to counseling, and needs for improved training on firearm safety counseling in medical education to inform the development of future education on clinical strategies for firearm injury prevention. Method A 2018 survey administered to 218 residents and fellows at a large, academic medical center asked about medical training on firearm injury prevention, frequency of asking patients about firearm access, and perceived barriers. Results The most common barriers cited were not knowing what to do with patients’ answers about access to firearms (72.1%), not having enough time (66.2%), not feeling comfortable identifying patients at-risk for firearm injury (49.2%), and not knowing how to ask patients about firearm access (48.6%). Prior education on firearm injury prevention was more strongly associated with asking than was personal exposure to firearms: 51.5% of respondents who had prior medical education reported asking compared with who had not received such education (31.8%, p=0.004). More than 90% of respondents were interested in further education about interventions, what questions to ask, and legal mechanisms to separate dangerous people from their firearms. Conclusions Education on assessing risk for firearm-related harm and, when indicated, counseling on safe firearm practices may increase the likelihood clinicians practice this behavior, though additional barriers exist.